Optimizing the external optical cavity parameters for performance improvement of a fiber grating fabry-perot laser - Hisham, H.K.; Abas, A.F.; Mahdiraji, G.A.; Mahdi, M.A.; Adikan, Faisal Rafiq Mahamd (OPTICAL SOC JAPAN, KUDAN-KITA BLDG 5F, 1-12-3, KUDAN-KITA CHIYODA-KU, TOKYO, 102, JAPAN, 2015)
The effects of the external optical cavity parameters (external optical cavity length (L-ext), amplitude coupling (C-o) and anti-reflection coating (ARC) reflectivity coefficients) on the noise and modulation spectra of a fiber grating Fabry-Perot laser are numerically analyzed for designing a laser that operates in strong feedback regime (Regime V). Fiber Bragg grating (FBG) is used as a wavelength selective element to control the properties of the laser output by controlling the external optical feedback (OFB) level. The study is performed by modifying a set of rate equations that are solved by considering the effects of external OFB and ambient temperature (T) variations. We proposed a model to calculate the temperature dependence (TD) of laser characteristics according to the TD of laser parameters. An accurate analytical expression for the TD of threshold carrier density (N-th,N- fe) has been derived. The TD of N-th,N- fe was calculated according to the TD of laser cavity parameters instead of using well-known empirical Pankove relationship via the use of characteristics temperature (T-o) and current (I-o). Results show that the optimum external fiber length (L-ext) is 3.1 cm. Also, it is shown that ARC with reflectivity value of 1 x 10(-2) is sufficient for the laser to operate at low noise, good modulation response, and low fabrication complexity.